2014
DOI: 10.1242/jeb.093203
|View full text |Cite
|
Sign up to set email alerts
|

Glottal opening and closing events investigated by electroglottography and super-high-speed video recordings

Abstract: Previous research has suggested that the peaks in the first derivative (dEGG) of the electroglottographic (EGG) signal are good approximate indicators of the events of glottal opening and closing. These findings were based on high-speed video (HSV) recordings with frame rates 10 times lower than the sampling frequencies of the corresponding EGG data. The present study attempts to corroborate these previous findings, utilizing super-HSV recordings. The HSV and EGG recordings (sampled at 27 and 44 kHz, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 43 publications
(50 reference statements)
1
30
0
Order By: Relevance
“…[36][37][38] As can be seen in Figure 1C, P SubN and SP N were relatively low in falsetto, whereas Flow N was relatively high. The opposite was observed for chest register.…”
Section: Vocal Registermentioning
confidence: 81%
“…[36][37][38] As can be seen in Figure 1C, P SubN and SP N were relatively low in falsetto, whereas Flow N was relatively high. The opposite was observed for chest register.…”
Section: Vocal Registermentioning
confidence: 81%
“…to exclude circa 22% of potential subjects, mainly due to the EGG derivative being too noisy. The results obtained by Herbst et al [83] using super-high-speed filming also showed that peaks in the first derivative of the EGG do not always coincide with the exact moments of glottal opening and closing. The waveform-reflecting parameter, SQ, and spectral parameters calculated for the glottal waveform seemed to weakly distinguish phonation types in the present material.…”
Section: Discussionmentioning
confidence: 93%
“…The duration of contact increased from about 34% of the glottal cycle before the register break to about 67% after the register break. In this example, calculation of the contact duration was performed from the positive and negative peaks in the dEGG signal, which have been shown to be roughly (but not precisely) representative of glottal closure and opening incidents (Herbst et al, 2014). This relative contact duration and its development over time can also be recognized in the dEGG wavegram ( Figure 2D), indicated by the horizontal dark and light lines.…”
Section: Electroglottography: Methodsmentioning
confidence: 95%